Using a model of the performance measures in Soft Systems Methodology (SSM) to take action: a case study in health care - Katherine Kotiadis; Antuela Tako; Etienne A.J.A. Rouwette; Christos Vasilakis; J. Brennan; P. Gandhi; H. Wegstapel; F. Sagias; P. Webb (2013)
This paper uses a case study of a multidisciplinary colorectal cancer team in health care to explain how a model of performance measures can lead to debate and action in Soft System Methodology (SSM). This study gives a greater emphasis and role to the performance measures than currently given in typical SSM studies. Currently, the concept of performance measurement in SSM is in the form of a set of criteria used to judge the performance of the SSM model (the purposeful activity model). These performance criteria are definitions of efficacy, efficiency, effectiveness, ethicality and elegance. However, the use of performance measures within SSM is not clear and therefore criticized by some as nebulous. This paper uses a case study to explain how to involve the stakeholders in deriving a performance measurement model (PMM), which is a more detailed expansion of the performance criteria. The paper concludes with some reflections about how the PMM can fit in the SSM cycle, with two modes of practice put forward.